Budget allocation for optimal performance of a university through adjusted-program-budget marginal-analysis - Maijama'a, Bilkisu (2019)
A strategic plan designed by universities globally, as well as in Malaysia, is used asa key indicator of progress using key performance indicators (KPIs) in assessing and equipping the universities with challenges of the educational needs in this millennium. Unfortunately, some universities set up their specific strategies to achieve their KPIs without much consideration to the limited available resources. Particularly, less attention is given to the cost and marginal cost of achieving the KPIs. This research therefore proposes the implementation of adjusted-program-budgeting-marginal-analysis (adjusted-PBMA), an approach used to accommodate both financial and quality output with transparency to allocate the available budget on KPIs, through minor-adjustments on the existing PBMA. Firstly, the similarities between the steps under PBMA and the steps involved in constructing the strategic plan for a university were identified. Next, adjustments were made by suggesting the application of marginal cost and cost consequence analysis to replace the existing qualitative approach in prioritizing the strategies, and the application of integer programming models (IP-Models) for the budget allocation process. The outcome was the new proposed adjusted-PBMA. To illustrate the applicability of the proposed adjusted-PBMA, a case study on Universiti Utara Malaysia for its student development agenda to achieve a six-star SETARA rating was conducted. Six possible IP-Model were developed. The optimal results were obtained, discussed, and compared. This adjusted-PBMA is useful and suitable for other organisations with KPI-oriented programs having limited budget allocation.